Socialization and Creation of Entrepreneurial Products for Class XII Tritech Informatics Accounting Vocational School Medan - Harianto, Adi; Chandra, Kuandi; Fakhrul Hirzi, M.; Arahman, Hamjah; Rivai, Ahmad; Budiman, Indra; Wijaya, Elyzabeth; Susanto, Agus; Restu Razaq, Mhd.; Nasib (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the current era of globalization and information technology, entrepreneurship is an important key in developing one's potential and helping drive the economy at various levels of society. The Medan Tritech Informatics Vocational High School (SMK) Accounting as one of the vocational secondary education institutions plays a role in equipping its students with entrepreneurial skills. Entrepreneurship refers to the process of creating, managing and developing a new venture or business, with the aim of generating profits. It involves various activities such as identifying business opportunities, developing product or service ideas, designing a business plan, gathering necessary resources (such as capital and labor), and managing day-to-day business operations.